Pengembangan Media Edukasi Gizi Nutriplay Serta Pengaruhnya Terhadap Perilaku Tentang Gizi Seimbang Siswa Sekolah Dasar - Fikri Khair Naqli; Annisa Rizkiriani (Media Kesehatan Politeknik Kesehatan Makassar, 2024)
Nutrition is one of the most common health problems in Indonesia. Being under or overnourished will affect their development. Children who are malnourished will experience reduced physical, cognitive and mental growth. In order to improve knowledge, attitudes and practices of healthy food selection, school-age children need nutrition education. Providing nutrition education can be done using various media such as visual media. This research is a quasy experimental research with pre-post intervention study. The population was students at SDN Kedunghalang 2 Bogor. The samples in the intervention and control groups were 5th grade students at SDN Kedunghalang 2 Bogor who were selected using purposive sampling technique. The data were analysed by inferential statistics using paired sample t-test, Wilcoxon test, independent sample t-test, and Mann-Whitney test. This study included 47 grade 5 students at SDN Kedunghalang 2 Bogor. Total female subjects were 26 and male subjects were 21. A total of 18 people stated that nutriplay media is very interesting as a nutrition education media. There was a significant increase in knowledge in the intervention and control groups. However, there were no significant differences in attitudes and practices between the two groups. Nutriplay is a nutrition education media that can be well received by elementary school students and can increase subject knowledge. The attitudes and practices of the subjects did not improve significantly because it takes a long time and there is a need for the involvement of teachers and families in nutrition education programmes, so it is better not only the role of students to be involved in providing nutrition education. Keywords: Nutriplay; diary; nutrition education; school children